Lidocaine infusion has a 25% opioid-sparing effect on background pain after burns: A prospective, randomised, double-blind, controlled trial. Issue 2 (March 2020) - Abdelrahman, Islam; Steinvall, Ingrid; Elmasry, Moustafa; Sjoberg, Folke
Highlights: We investigated the opioid sparing effect of lidocaine when treating background pain in burns. Adult patients were randomised to have either lidocaine infusion or a placebo infusion, for seven consecutive days. The opioid consumption in the lidocaine group declined by roughly 25% during the period of the study. An intravenous infusion of lidocaine was safe and had an opioid-sparing effect. Abstract: Background: The pain of a burn mainly results from the inflammatory cascade that is induced by the injured tissue, and is classified as background, breakthrough, procedural and postoperative pain. High doses of opioids are usually needed to treat background pain, so its management includes a combination of types of analgesia to reduce the side effects. Lidocaine given intravenously has been shown in two small, uncontrolled studies to have an appreciable effect on pain after burns. Objectives: In this prospective double-blind controlled trial we aimed to examine and quantify the opioid-sparing effect of a continuous infusion of lidocaine for the treatment of background pain during the early period after a burn. Methods: Adult patients injured with burns of >10 total body surface area burned (TBSA%) and treated with a morphine based patient-controlled analgesia device (PCA) were randomised to have either lidocaine infusion starting with a bolus dose (1 mg lidocaine/kg) followed by continuous infusion (180 mg lidocaine/hour) or a placebo infusion, for seven consecutive days. Total daily consumption of opioids (mg) and amount of pain (visual analogue score, VAS) were recorded. Results: We included 19 patients, 10 of whom were given a lidocaine infusion. There were no differences between groups in VAS, TBSA%, time of enrolment to the study since the initial burn, or duration of hospital stay. The opioid consumption in the lidocaine group declined by roughly 25% during the period of the study. Conclusion: An intravenous infusion of lidocaine was safe and had an opioid-sparing effect when treating background pain in burns.